An aggregation of instruments for critical assessments of economic evaluations - Emmert, Martin; Huber, Maria; Schöffski, Oliver (PharmacoEconomics German Research Articles, 2011)
<p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Objective  <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Due to an increasing number of economic evaluations, critical assessments are gaining in importance. To date, the available assessment tools possess different focuses, making their results difficult to compare. After identifying and comparing the currently applied tools, we present an aggregated checklist which can be used as a guideline by both authors and reviewers of economic evaluations. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Methods  <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Peer-reviewed German and English language literature was searched in Medline via PubMed (2000–2009). Study selection was limited to systematic reviews, in which a critical assessment of the included economic evaluations was conducted. Furthermore, one representative assessment tool used in a health technology assessment (HTA) report was considered. Applied assessment tools were identified and recombined. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Results  <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> 107 systematic reviews provide a critical assessment of the evaluation studies. In total, nine different assessment tools were used. The checklist of the British Medical Journal (N = 49) and criteria defined by Drummond (N = 44) have been applied most frequently, three checklists were applied only once. Our aggregated checklist contains 99 criteria; they were assigned into four categories: study design (11 criteria), data (46 criteria), analysis and interpretation (24 criteria), and results (18 criteria). An increasing number of conducted systematic reviews and critical study appraisals could be demonstrated. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Conclusion  <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Considering the different focuses of the identified tools, applying several appraisal tools or adding specific criteria to an assessment tool may make sense. In future, our checklist can be used as a guideline for both authors and reviewers when conducting or assessing the quality of economic evaluations. Further research is needed on the validation of the instrument and the classification of the assessment results.
WiSo-Import:2015-03-26:4450